Simultaneous observation of direct and Raman-scattered O VI lines in the symbiotic nova RR telescopii - ESPEY, BRIAN RUSSELL (American Astronomical Society, 1995)
The optical spectra of some symbiotic binaries show two lines in the red region of the spectrum that cannot be identified with any known allowed or forbidden transitions. A case has been made that these lines are Raman-scattered O VI lambda lambda 1032, 1038 emission lines. We present simultaneous far-UV and optical spectra of the symbiotic nova RR Tel, obtained with the Hopkins Ultraviolet Telescope and the Anglo-Australian Telescope during the Astro-2 Space Shuttle mission. These data show the first coincident detection of the strong O VI lambda lambda 1032, 1038 doublet and lambda lambda 6825, 7082 emission lines. The latter display strong linear polarization and provide new information on the structure of the nebular material. Our observations provide strong evidence for the Raman effect in RR Tel.
PUBLISHED
Keywords: Physics